1973
DOI: 10.1159/000259855
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride Concentrations in Deciduous Teeth of Children Using Fluoride Mouthrinses

Abstract: Analysis of exfoliated deciduous teeth from children living in both fluoridated and non-fluoridated areas and who used a 0.02% F rinse 5 times per week or a 0.1% F rinse one time per week revealed that significant fluoride was acquired only at a depth of 5 μm from the surface. Children who used the dilute F rinse in the non-fluoridated area acquired approximately one-third as much fluoride as teeth from the other groups. Enamel was not found to increase in fluoride concentration as more rinses were received bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…15 The mean F + uptake from the control and experimental groups of both mouthrinses were found to be at 594.5 ppm and 781.4 ppm, respectively. These figures were close to the findings of Kohli et al 14 with 578 ppm and Mellberg et al 19 with 563 ppm in the same depth of biopsy. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…15 The mean F + uptake from the control and experimental groups of both mouthrinses were found to be at 594.5 ppm and 781.4 ppm, respectively. These figures were close to the findings of Kohli et al 14 with 578 ppm and Mellberg et al 19 with 563 ppm in the same depth of biopsy. …”
Section: Discussionsupporting
confidence: 91%
“…14,17,18 It is believed that enamel biopsy provides a direct measurement as one of the most reliable techniques for measuring F + level of enamel. 19,20 Root and Schreiber 20 reported that long-term use of fluoride rinse has a greater chance of F + uptake by enamel than short periods, indicating a more reliable preventive role when fluoride rinse is used regularly. It is worth pointing out that the use of enamel biopsy, which was first introduced by McCann, 12 has frequently been reported to be used by many researchers who have employed 0.5 mol perchloric acid for 30 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…It is also concluded that the fiuoride increment lof the sound enamel surface is not a suitable predictor of the cariostatic potential of 0.2% neutral NaF mouthrinse procedure, confirming suggestions made earlier by MELLBERG ^/ al. (18) and by BRUUN & STOLTZE (8). Enamel fiuoride biopsies for this purpose will therefore find little use in public health dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…However, from correlations of in vivo fluoride uptake with inhibition of dental caries after use of various fluoride preparations,5 6 there is evidence that preparations that do not deposit large amounts of fluoride in enamel can be as effective in preventing decay as preparations that deposit significant amounts of fluoride. In each of the studies where this finding was made, the preparation was used on a daily or a weekly basis.…”
Section: Discussionmentioning
confidence: 99%